Effects of Muscle Energy Technique on Pain and Range of Motion in Chronic Low Back Pain Subjects with Lateral Flexion Restriction - Mazidavi, Ali; Karimi, Noureddin; Khorasani, Bijan; Baraghoosh, Parastoo; Biglarian, Akbar (Physical treatments, 2023)
Purpose: Low back pain (LBP) is a common problem with a significant impact on individuals and society, leading to activity limitation and chronic pain. Quadratus lumborum (QL) muscle tightness can trigger symptoms of significant LBP. Muscle energy technique (MET), a gentle manual therapy for restricted motion in the spine and limbs, aims to induce muscle relaxation, reduce pain, and improve range of motion (ROM). The aim of this study was to investigate the effects of MET on pain reduction and ROM improvement in chronic LBP subjects with lateral flexion restriction. Methods: This study was a randomized single-blind clinical trial. One hundred and two participants diagnosed with chronic LBP and lateral flexion restriction were randomly divided into two groups: Control (n=51) and intervention (n=51). The control group received conventional physiotherapy, while the intervention group was provided with a combination of conventional physiotherapy and MET (post-isometric relaxation). Pain and ROM were measured using the visual analogue scale (VAS) and a goniometer, respectively. Both groups were evaluated before and immediately after the treatment. Results: The results revealed a significant reduction in pain and improvement in ROM in both groups after the treatment. No significant differences were found in the mean pain scores between the two groups (P=0.77). However, the mean scores of ROM in the intervention group showed a significant difference compared to the control group (P≤0.001). Conclusion: MET combination with conventional physiotherapy significantly improves LBP and ROM of lateral flexion in chronic LBP subjects with lateral flexion restriction.